2005
DOI: 10.1124/dmd.104.002972
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION AND PARTIAL PURIFICATION OF THE RAT AND HUMAN ENZYME SYSTEMS ACTIVE IN THE REDUCTION OFN-HYDROXYMELAGATRAN AND BENZAMIDOXIME

Abstract: ABSTRACT:The enzymic basis for intracellular reduction of N-hydroxylated amidines to their corresponding amidines, and hydroxylamines to their corresponding amines, is unknown. The hydroxylated amidines can be used as prodrug moieties, and an understanding of the enzyme system active in the reduction can contribute to more efficient drug development. In this study, we examined the properties of this enzyme system using benzamidoxime and N-hydroxymelagatran as substrates. In rats and humans, the hepatic enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…Enzyme Kinetics of the Amidoxime Reductase-The enzyme kinetics of the amidoxime reductase enzyme system were characterized using subcellular fractions isolated from rat and human liver in the absence and presence of the inhibitor potassium cyanide (KCN) (6). The reductase activity observed in the presence of KCN is considered to be the nonspecific reductase activity, especially at higher benzamidoxime concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Enzyme Kinetics of the Amidoxime Reductase-The enzyme kinetics of the amidoxime reductase enzyme system were characterized using subcellular fractions isolated from rat and human liver in the absence and presence of the inhibitor potassium cyanide (KCN) (6). The reductase activity observed in the presence of KCN is considered to be the nonspecific reductase activity, especially at higher benzamidoxime concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we found high amidoxime reductase activity preferentially in outer mitochondrial membranes (OMM) associated with adipose tissue, liver, and kidney (6). Furthermore, the reductase activity was dependent on the cofactor NADH and inhibited by potassium cyanide (KCN), whereas typical CYP inhibitors, such as carbon monoxide, were ineffective (6) indicating that the reductase is unlikely to be a cytochrome P450 as was suggested previously (10).…”
mentioning
confidence: 90%
See 3 more Smart Citations